Effect of sand fines concentration on the erosion-corrosion mechanism of carbon steel 90â¦ elbow pipe in slug flow - Khan, R. (MDPI AG, 2020)
Erosion-corrosion of elbow configurations has recently been a momentous concern in hydrocarbon processing and transportation industries. The carbon steel 90â¦ elbows are susceptible to the erosion-corrosion during the multiphase flow, peculiarly for erosive slug flows. This paper studies the erosion-corrosion performance of 90â¦ elbows at slug flow conditions for impact with 2, 5, and 10 wt. sand fines concentrations on AISI 1018 carbon steel exploiting quantitative and qualitative analyses. The worn surface analyses were effectuated by using laser confocal and scanning electron microscopy. The experiment was conducted under air and water slug flow containing sand fines of 50 Âµm average size circulated in the closed flow loop. The results manifest that with the increase of concentration level, the erosion-corrosion magnitude increases remarkably. Sand fines instigate the development of perforation sites in the form of circular, elongated, and coalescence pits at the elbow downstream and the corrosion attack is much more obvious with the increase of sand fines concentration. Another congruent finding is that cutting and pitting corrosion as the primitive causes of material degradation, the 10 wt. sand fines concentration in carrier phase increases the erosion-corrosion rate of carbon steel up to 93 relative to the 2 wt. sand fines concentration in slug flow. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.